Systematising troubleshooting of disputes in network - Sowmya K. B.; Thejaswini A. (Institute of Advanced Engineering and Science, 2021)
With the growing network size, virtualization everywhere, it is getting more difficult to configure and manage the network devices. Software Defined Networking (SDN) is a way to address these problems. Application Centric Infrastructure (ACI) is the Cisco’s solution to SDN, with centralized automation and policy-driven application profiles. If there is any bug in the network or problem with the expected functionality of the network, ACI cases are opened in the Technical Assistance Centre (TAC) for troubleshooting the issue. Engineers currently troubleshoot ACI cases manually by using Command Line Interface (CLI) and trace for different events triggered by the policy pushes by logs generated at different stages of the ACI and from different servers responsible for this, which indeed is a very tedious, time consuming task and is prone to manual errors. This paper describes a way to automate the entire ACI troubleshooting process with the user-friendly GUI which can show the entire information needed for troubleshooting by extracting relevant information at every layer. By making use of FSM models the proposed solution can be extended to other areas which involve log analysis using CLI to extract relevant information and is not just limited to ACI.